Land husbandry: an environmental challenge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Farming systems have been under serious threat in most of the sub-Saharan countries of Africa in recent times. This is a result of increasing population pressure, unstable economies both at national and international level, and changing climate....